Degradation of nonylphenol ethoxylate-9 (NPE-9) by photochemical advanced oxidation technologies - De La Fuente, Luciana (2010)
The applicability of different photochemical advanced oxidation technologies (PAOTs), namely, direct UV-C photolysis, UV-C/H2O 2 and UV-A/TiO2 heterogeneous photocatalysis (HP), and photo-Fenton reactions (UV-A/H2O2/Fe2+, PF), for the degradation of 300 mg L-1 nonylphenol ethoxylate-9 (NPE-9) in water is described. Different kinetic regimes for each PAOT were found, and as a result, comparative efficiencies could be obtained only from final parameters such as NPE-9 conversion, TOC decrease, and aldehyde production after 3 h of treatment. The initial photonic efficiencies indicate, however, that UV-A processes make better use of photons than UV-C processes. Preliminary optimization of PF systems showed that the most efficient NPE-9/H 2O2/Fe2+ molar ratio was 1:1:0.5. Degradation products were partially investigated. Fortunately, toxic 4-nonylphenol was never found as a byproduct of the degradation after any of the treatments. Aldehydes were formed in all of the processes, but they appeared at a low extent in PF reactions. Therefore, PF treatments were considered to be the best degradation processes. © 2010 American Chemical Society.